Arte y fotografía en la prensa mexicana. La primera exposición de arte de los fotógrafos de prensa en 1911 - Daniel Escorza Rodríguez (L'Ordinaire des Amériques)
The purpose of this paper is to explore the aesthetics of photography produced by press photographers during the first decade of the 20th century. We are specifically going to review how the First Exhibition of Photographic Art was organized and developed, sponsored by the Society of Metropolitan Press Photographers, and inaugurated on December 18, 1911. Beyond just describing the event and the possible identification of the exhibited images, this work will focus on analyzing the concept of art and photography among the photographers who exhibited their work for the first time, such as Agustín Casasola, Manuel Ramos, Gerónimo Hernández, Ezequiel Alvarez Tostado, Antonio Garduño and Samuel Tinoco, among some other Mexican photographers from the early 20th century.